2015
DOI: 10.1007/s00394-015-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Grape skin extract-derived polyphenols modify programming-induced renal endowment in prenatal protein-restricted male mouse offspring

Abstract: The treatment of low-protein-fed dams during pregnancy with ACH09 provides protection from early-life deleterious renal morphological changes. The protective effect of ACH09 may involve antioxidant action and vasodilator effect of the extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Similar effects have been found with soy genistein-rich diets; specifically decreased oxidative stress and beneficial effects on the cardiovascular system, lowering incidence of hypertension [ 104 ]. The stilbene resveratrol has comparable positive effects on oxidative stress and metabolism in adults [ 105 , 106 ] and there is experimental evidence that ameliorates embryonic oxidative stress and apoptosis associated with diabetic embryopathy, preventing developmental delays in embryos of diabetic dams and, afterwards, glomerular loss and renal immaturity in fetuses [ 107 , 108 , 109 , 110 ].…”
Section: Polyphenols and In Vivo Reproductive Eventsmentioning
confidence: 99%
“…Similar effects have been found with soy genistein-rich diets; specifically decreased oxidative stress and beneficial effects on the cardiovascular system, lowering incidence of hypertension [ 104 ]. The stilbene resveratrol has comparable positive effects on oxidative stress and metabolism in adults [ 105 , 106 ] and there is experimental evidence that ameliorates embryonic oxidative stress and apoptosis associated with diabetic embryopathy, preventing developmental delays in embryos of diabetic dams and, afterwards, glomerular loss and renal immaturity in fetuses [ 107 , 108 , 109 , 110 ].…”
Section: Polyphenols and In Vivo Reproductive Eventsmentioning
confidence: 99%
“…On each experiment day, the pigs received a single dose of one of two treatments: red cabbage or grape skin extracts at one of four doses: 0, 2.22, 4.44, and 11.11 mg GAE/kg BW. Considering that the grape skin extract had a higher total phenolic content compared to the red cabbage extract, the doses were selected based on previous studies of grape skin extract administered safely to mice [ 49 , 50 , 51 ]. The maximal dose of 11.11 mg GAE/kg BW corresponding to 30 mg grape skin extract/kg BW was selected for our pig study, as this dose is equivalent to the proven safe dose of 200 mg grape skin extract/kg BW in mice [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress and inflammation are major contributors to vascular remodeling and hypertension ( 106 ). In LP ( 94 , 107 ) and maternal smoking models ( 108 ), it was shown that oxidative stress during critical developmental steps may significantly contribute to renal susceptibility toward disease. In addition, both IUGR offspring after global undernutrition of the dam ( 109 ) and after high-fat died during gestation and lactation ( 110 ) showed increased oxidative stress and elevated blood pressure later in life.…”
Section: Mechanisms Of Renal Programmingmentioning
confidence: 99%